Cerita Klasik “Tantri Kamandaka” sebagai Sumber Ekonomi Kreatif - I Nyoman Suarka; AA. Gede Bawa (Jurnal Kajian Bali (Journal of Bali Studies), 2018)
This study aims to analyze a classical literary Tantri Kamandaka text as creative economic resources. This research a empts to o er the idea of literary studies to the downstream of research results that can be utilized as much as possible for the welfare of the community. As with the text of Tantri Kamandaka, in addition to being a medium of the nation’s character values, it can also be empowered as creative economic resources or cultural industry. This research made use of content analysis model and medium transfer study. The method used was a method of creating art works by covering the exploratory stage, the exploring activity to uncover the sources of ideas was based on the reading and comprehending Tantri Kamandaka text; the design stage was visualizing the results of ideas exploration into sketches or alternative design to nal draft; and the stage of embodiment, which was to establish the nal design into a prototive model until the perfect work was created in accordance with the ideas. The results show that the text of Tantri Kamandaka potential as a source of creative economy, especially as a source of inspiration for the creation of creative economic product designs.